2016
DOI: 10.5604/17331331.1227668
|View full text |Cite
|
Sign up to set email alerts
|

High Seroprevalence of CMV Among Women of Childbearing Age Implicates High Burden of Congenital Cytomegalovirus Infection in Poland

Abstract: Cytomegaloviruses are common worldwide, with variable frequency of infections. The infection in pregnancy may lead to pregnancy loss or serious sequelae for the child. To understand the risk posed by CMV in Poland we conducted cross-sectional study on women aged 15-49 basing on existing serum bank. Age dependent incidence, the rates of congenital infection and sequelae were modelled from sero-prevalence, literature and demographic data. The overall anti-CMV IgG prevalence was 81.9% increasing from 74.3% in <30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 37 publications
3
15
0
Order By: Relevance
“…Siennicka et al (2009) reported that seropositivity rate for VZV was approximately 98% in a group of 19-year-olds from Poland. The same author conducted a study among women of childbearing age, where the overall anti-CMV IgG seropositivity was 81.9% (Siennicka et al, 2016). Data regarding seroprevalence of other herpesviruses in general population in Poland is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Siennicka et al (2009) reported that seropositivity rate for VZV was approximately 98% in a group of 19-year-olds from Poland. The same author conducted a study among women of childbearing age, where the overall anti-CMV IgG seropositivity was 81.9% (Siennicka et al, 2016). Data regarding seroprevalence of other herpesviruses in general population in Poland is limited.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the prevalence of CMV IgG antibodies among women in other countries was similar to that in Poland. 9 Like in Poland, CMV IgG seroprevalence among the nurses studied, though high, is not higher than among the population of reproductive-age women. 9,10 EBV VCA IgG antibodies were found in all the nurses covered by the study as well as in all the participants in the control group.…”
Section: Discussionmentioning
confidence: 72%
“…9 Like in Poland, CMV IgG seroprevalence among the nurses studied, though high, is not higher than among the population of reproductive-age women. 9,10 EBV VCA IgG antibodies were found in all the nurses covered by the study as well as in all the participants in the control group. These results are consistent with the results of studies of the EBV seroprevalence in different populations worldwide.…”
Section: Discussionmentioning
confidence: 72%
“…It has also been reported that at birth or in the first 2-3 weeks of life, it is essential to use appropriate tests for cCMV diagnosis, but after 2-3 weeks of life, the diagnosis of congenital infection could only be suspected on clinical grounds [29]. Moreover, in a cross-sectional study from Poland, based on data from existing serum bank from women aged 15-49, the estimated rate of cCMV varies from 22.4-37.2 per 1,000 live births, depending on the assumptions made [18]. As presented in Figure 1, a large variability in incidence was observed over the study period.…”
Section: Resultsmentioning
confidence: 99%
“…A study from two European countries that focused on CMV screening in newborns in 1977-1986 estimated the incidence of congenital infections in infants at the level of 4.6 cases per 1,000 births in Malmö, and 3.2 cases per 1,000 births in London [17]. Information on cCMV in Poland is limited or based on case reports [18,19,20,21,22]. Due to its clinical and public health importance, recent data on cCMV epidemiology in Poland should be investigated.…”
Section: Introductionmentioning
confidence: 99%